2011
DOI: 10.1590/s0102-86502011000100007
|View full text |Cite
|
Sign up to set email alerts
|

Miniplate 1.5 fixation for the repair of mandibular osteotomies in cats

Abstract: Purpose: To evaluate the application of the maxillofacial miniplate 1.5 in the repair of unilateral mandibular osteotomies in cats. Methods: Twelve adult cats were divided into two groups. In group 1 (n=6), the osteotomy was performed in the body of the mandible, behind the 1st molar. In group 2 (n=6), the osteotomy was performed between the 4th premolar and 1st molar. The osteotomy was fixed with a titanium miniplate 1.5. Oral alimentation was reinitiated 24 hours after surgery. Cats were euthanized at 12 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The microscopic images of the Goldner's trichrome stained sections were obtained using Axioskop microscopy (Olympus BX51, Olympus, Japan). The mature bone matrix, immature new bone matrix, and calcified cartilage were stained green, red, and pale green, respectively …”
Section: Methodsmentioning
confidence: 99%
“…The microscopic images of the Goldner's trichrome stained sections were obtained using Axioskop microscopy (Olympus BX51, Olympus, Japan). The mature bone matrix, immature new bone matrix, and calcified cartilage were stained green, red, and pale green, respectively …”
Section: Methodsmentioning
confidence: 99%
“…20 Biomechanical cadaver studies have also shown that six-hole miniplates can be successfully applied to the ventrolateral caudal mandible. 19,28 Rigid reconstruction and reestablishment of normocclusion immediately improves both the comfort of the patient and jaw function. not necessarily preclude the use of a titanium miniplate.…”
Section: Titanium Miniplatesmentioning
confidence: 99%
“… 20 Biomechanical cadaver studies have also shown that six-hole miniplates can be successfully applied to the ventrolateral caudal mandible. 19 , 28 …”
Section: Mandibular Fracture Repairmentioning
confidence: 99%
“…However, the terms hemimandible and halves of the mandible are still widely used in the veterinary literature. 1-10…”
mentioning
confidence: 99%
“…The use of these implants is well described in the surgical literature and these techniques provide adequate stability for mandibular fractures, especially comminuted fractures. 2-4,8,10,16,17 The different configurations of external skeletal fixator for the stabilisation of mandibular fractures have been previously reported. 10 Placement of pins from side to side in the rostral aspect of the mandible has been reported in dogs and cats without causing interference with tongue function.…”
mentioning
confidence: 99%